1958
DOI: 10.1172/jci103764
|View full text |Cite
|
Sign up to set email alerts
|

The Passage of Ammonia Across the Blood-Brain-Barrier and its Relation to Blood pH

Abstract: Ammonium salts have been shown to have significantly different toxicities (LD,0's) when administered intravenously under controlled conditions (1). This differential toxicity appeared to be related to the change in blood pH induced by each salt.The normal blood pH (7.4) is close enough to the pKbh of ammonia,2 approximately 8.90 at 370 C. (2), so that any change in blood pH would significantly affect the ratio of unionized (NH8) to ionized (NH4+) ammonia. Based on two factors, the greater tissue permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1959
1959
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 15 publications
1
15
0
2
Order By: Relevance
“…Although we did not measure blood pH, these findings are consistent with the fre quent dem onstration of metabolic alkalosis secondary to urinary po tassium and chloride loss following chlorothiazide and meralluride [2,4,11,14,17,18,20,21,27]. Since metabolic alkalosis has been shown to increase the toxicity of a given ammonia load [28], our results suggest th at the production of encephalopathy following diu retics, especially chlorothiazide, is due to the interrelated effects of hyperam monem ia, hypokalemia and alkalosis.…”
Section: Hemodynamicsupporting
confidence: 79%
“…Although we did not measure blood pH, these findings are consistent with the fre quent dem onstration of metabolic alkalosis secondary to urinary po tassium and chloride loss following chlorothiazide and meralluride [2,4,11,14,17,18,20,21,27]. Since metabolic alkalosis has been shown to increase the toxicity of a given ammonia load [28], our results suggest th at the production of encephalopathy following diu retics, especially chlorothiazide, is due to the interrelated effects of hyperam monem ia, hypokalemia and alkalosis.…”
Section: Hemodynamicsupporting
confidence: 79%
“…During metabolic and respiratory alkalosis brain and muscle ammonia concentrations increased two-to threefold, while during metabolic and respiratory acidosis brain and muscle concentrations remained at or decreased below control concentrations. 4. Explanation for these findings may be found in the pH gradient drug distribution hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…Recently a direct relationship between an increase in blood pH and the diffusion of ammonia from blood into tissues has been suggested (2). Other investigators have demonstrated greater toxicity of the more alkaline ammonium salts (3) and that an increase in blood pH enhanced passage of ammonia into the brain of mice (4).…”
mentioning
confidence: 98%
“…Extracellular metabolic alkalosis is detrimental to the patient because it encourages ammonia to enter cells. Warren & Nathan (1958) have demonstrated the increased toxicity in mice of alkaline as opposed to acid ammonium salts. Patients have been treated by acid infusions and though blood and CSF ammonia levels respond appropriately no clinical improvement results.…”
Section: The Cellmentioning
confidence: 99%